A higher-cost region excessively attracts firms. Issue 1 (2nd January 2021) - Kurata, Hiroshi; Ohkawa, Takao; Okamura, Makoto
Abstract : This study examines the economic efficiency associated with firm location in a non-traded goods industry. This industry comprises of two segmented regions (markets) and a fixed number of potentially identical, oligopolistic firms. We consider the following two-stage game. In the first stage, firms determine the region in which they want to locate simultaneously and independently. In the second, given the pattern of firm location, every firm engages in Cournot competition in each market. If a potentially identical firm is located in a different region, the firm has a different cost function, and therefore, different fixed and marginal costs. Thus, the cost function of each firm is not firm-specific but region-specific. We define welfare as the sum of the region's social surplus, which includes consumer surplus and producer surplus. We obtain the following results. First, when only the marginal costs differ across regions, from a welfare perspective, an insufficient number of firms are located in the higher-cost region. Second, when only the fixed costs differ across regions, an excessive number of firms are located in the higher-cost region. Third, when a region has sufficiently higher fixed and marginal costs than another, an excessive number of firms are located in this region.